Comparison of inflammatory responses and muscle damage indices following a soccer, basketball, volleyball and handball game at an elite competitive level - Souglis, A.; Bogdanis, G. C.; Giannopoulou, I.; Papadopoulos, C.; Apostolidis, N. (Research in Sports Medicine, 2015)
Inflammatory responses and muscle damage indices were compared between four popular team sports at an elite level. Seventy two male elite players of four team sports: soccer (n = 18), basketball (n = 18), volleyball (n = 18) and handball (n = 18), completed an official match, while 18 non-athletes served as controls. Blood samples were drawn before, immediately after and 13 and 37 h post-match. Soccer produced the greatest increase in inflammatory cytokines (tumor necrosis factor-alpha and interleukin-6), which were increased by 3-4 fold immediately after the game, as well as in C-reactive protein, which was increased by threefold in the next morning after the match. Metabolic stress (urea, ammonia and cortisol) and muscle damage indices (creatine kinase and lactate dehydrogenase) were also higher after soccer, with creatine kinase responses being almost 2-3 times higher than the other sports. Volleyball showed the smallest increase in inflammation and muscle damage markers compared with the other three sports.